Long-term effect of exercise training in patients after transcatheter aortic valve implantation: Follow-up of the SPORT:TAVI randomised pilot study - Pressler, Axel; Foerschner, Leonie; Hummel, Jana; Haller, Bernhard; Christle, Jeffrey W.; Halle, Martin (European Journal of Preventive Cardiology, 2018)
Background: Increased exercise capacity favourably influences clinical outcomes after transcatheter aortic valve implantation. In our SPORT:TAVI randomised pilot trial, eight weeks of endurance and resistance training (training group, TG) shortly after transcatheter aortic valve implantation resulted in significantly improved exercise capacity, muscular strength and quality of life compared to usual care (UC). However, the long-term clinical benefits of such an intervention are unknown. Design: A randomised controlled trial. Methods: SPORT:TAVI participants underwent reassessment of trial endpoints 24 ± 6 months after baseline: maximal oxygen uptake (VO 2 peak) and anaerobic threshold (VO 2 AT) were assessed with cardiopulmonary exercise testing, muscular strength with one-repetition maximum testing, quality of life with the Kansas City cardiomyopathy and medical outcomes study 12-item short-form health survey questionnaires, and prosthetic aortic valve function with echocardiography. Results: Of 27 original participants (TG 13; UC 14; age 81 ± 6 years), more patients had died during follow-up in UC (n = 5) than in TG (n = 2; P = 0.165); three further patients (TG 1; UC 2) were unavailable for other reasons. In the remaining patients (TG 10; UC 7), a significant between-group difference in favour of TG was observed for change in VO 2 AT from baseline (2.7 ml/min/kg (95% confidence interval 0.8–4.6); P = 0.008), but not for change in VO 2 peak (2.1 ml/min/kg (–1.1–5.4); P = 0.178). Changes in muscular strength and quality of life did not differ between groups over time. Overall, prosthetic valve function remained intact in both groups. Conclusions: Eight weeks of exercise training shortly after transcatheter aortic valve implantation resulted in preserved long-term improvements in VO 2 AT, but not VO 2 peak, muscular strength or quality of life compared to usual care. The findings emphasise the importance of ongoing exercise interventions following transcatheter aortic valve implantation to maintain initial improvements long term. Clinical Trial Registration (original trial): Clinicaltrials.gov NCT01935297.
CRIS-Team Scopus Importer:2023-03-08
Keywords: exercise training; quality of life; Transcatheter aortic valve implantation